Repetitive use of levosimendan in advanced heart failure: need for stronger evidence in a field in dire need of a useful therapy. (15th September 2017) - Pölzl, Gerhard; Altenberger, Johann; Baholli, Loant; Beltrán, Paola; Borbély, Attila; Comin-Colet, Josep; Delgado, Juan F.; Fedele, Francesco; Fontana, Antonella; Fruhwald, Friedrich; Giamouzis, Gregory; Giannakoulas, George; et al.
Abstract: Patients in the latest stages of heart failure are severely compromised, with poor quality of life and frequent hospitalizations. Heart transplantation and left ventricular assist device implantation are viable options only for a minority, and intermittent or continuous infusions of positive inotropes may be needed as a bridge therapy or as a symptomatic approach. In these settings, levosimendan has potential advantages over conventional inotropes (catecholamines and phosphodiesterase inhibitors), such as sustained effects after initial infusion, synergy with beta-blockers, and no increase in oxygen consumption. Levosimendan has been suggested as a treatment that reduces re-hospitalization and improves quality of life. However, previous clinical studies of intermittent infusions of levosimendan were not powered to show statistical significance on key outcome parameters. A panel of 45 expert clinicians from 12 European countries met in Rome on November 24–25, 2016 to review the literature and envision an appropriately designed clinical trial addressing these needs. In the earlier FIGHT trial (daily subcutaneous injection of liraglutide in heart failure patients with reduced ejection fraction) a composite Global Rank Score was used as primary end-point where death, re-hospitalization, and change in N-terminal-prohormone-brain natriuretic peptide level were considered in a hierarchical order. In the present study, we tested the same end-point post hoc in the PERSIST and LEVOREP trials on oral and repeated i.v. levosimendan, respectively, and demonstrated superiority of levosimendan treatment vs placebo. The use of the same composite end-point in a properly powered study on repetitive levosimendan in advanced heart failure is strongly advocated.